Eating the alphabet : fruits and vegetables from A to Z - Ehlert, Lois. (Orlando, Fla. : Harcourt Brace, 1989)
An alphabetical tour of the world of fruits and vegetables, from apricot and artichoke to yam and zucchini.
Wilson's Children, October 2010.
School Library Journal, May 1997.
Book Links (A.L.A.), October 2008.
Booklist starred, December 1996.
Publisher's Weekly, November 1995.
Booklist, May 1996.
Keywords: Vegetables -- Juvenile literature; Fruit -- Juvenile literature; English language -- Alphabet -- Juvenile literature; Vegetables; Fruit; Alphabet; Vegetables; Fruit; Alphabet; English language -- Alphabet; Alphabet; Fruit; Vegetables